Laser Doppler Assessment of Vasomotor Axon Reflex Responsiveness to Evaluate Neurovascular Function - Kubasch, Marie Luise; Kubasch, Anne Sophie; Torres Pacheco, Juliana; Buchmann, Sylvia J.; Illigens, Ben Min-Woo; Barlinn, Kristian; Siepmann, Timo (Frontiers in Neurology, 2017)
The vasomotor axon reflex can be evoked in peripheral epidermal nociceptive C-fibers to induce local vasodilation. This neurogenic flare response is a measure of C-fiber functional integrity and therefore shows impairment in patients with small fiber neuropathy. Laser Doppler Flowmetry (LDF) and laser Doppler Imaging (LDI) are both techniques to analyse vasomotor small fiber function by quantifying the integrity of the vasomotor mediated axon-reflex. While LDF assesses the flare response following acetylcholine iontophoresis with temporal resolution at a single defined skin point, LDI records flare responses with spatial and temporal resolution, generating a two-dimensional map of superficial blood flow. LDF is characterized by a high intra- and interindividual measurement variability, which is smaller in LDI due to its spatial resolution. Nevertheless, LDI still lacks standardized methods for image analysis. Consequently, use of the technique currently remains on an experimental level. Here, we sought to review the current literature on laser Doppler assessment of vasomotor function and discuss potential future applications of established techniques as well as those that are still experimental.